2008
DOI: 10.5130/tfc.v3i2.922
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of Protest in Transnational Contexts: Indian Seamen Abroad, 1885-1945

Abstract: This paper offers a preliminary exploration of contexts and forms of protest and defiance of authority by Indian seafarers employed on ocean-going steam vessels over six decades to the end of World War II. Though relatively small in numbers and apparently untypical in many respects of a 'modern' industrial workforce, the study of Indian seafarers can shed interesting light on several wider aspects of Indian labour history. The transnational and trans-cultural context of employment of Indian seamen also helps i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Balachandran argues that because of their political vulnerability away from home, in colonial conditions, the Indians focussed on conflicts over contractual conditions like demands to transfer between ships or between ports, where they could defend their actions legally. 21 His depiction of a politically aware and strategically assertive body of seamen is supported by Tabili's research on Indian seafarers who had become resident in English port communities. 22 These tactics can all be traced in the Australian events.…”
Section: Indian Perceptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Balachandran argues that because of their political vulnerability away from home, in colonial conditions, the Indians focussed on conflicts over contractual conditions like demands to transfer between ships or between ports, where they could defend their actions legally. 21 His depiction of a politically aware and strategically assertive body of seamen is supported by Tabili's research on Indian seafarers who had become resident in English port communities. 22 These tactics can all be traced in the Australian events.…”
Section: Indian Perceptionsmentioning
confidence: 97%
“…Both the transfer to another shipping company, the transfer to vessels whose destination was NOT an Indian one and the transfer to another port were all actions contradictory to the Indian articles of agreement under which Indians were contracted and were precisely the circumstances to which Indians had developed strategic opposition in the past in the United Kingdom and in Australia. 76 The second source of labour was British India itself, and the Dutch received the active cooperation of the British colonial administration to recruit seamen in Bombay. The timing of the arrival and forced mobilisation of these replacement Indian crews was not well recorded in the early boycott, but it is clear that they had not been informed about the political role they would be fulfilling by sailing on the Dutch ships.…”
Section: The Indian Storymentioning
confidence: 99%
“…A few days later the Chief Superintendent (Scotland District) reported that he had “been informed by the Anchor Line that the Lascar Deck ratings who refused to transfer to the SS Britannia on the 2 nd instant have been released from Gaol and sent to Liverpool to join the Britannia ”. This suggests that contestation of transfers were used as moments of strategic leverage to win concessions (see also Balachandran 2008:60−61).…”
Section: Subaltern Agency and The Spatial Politics Of Circulationmentioning
confidence: 99%